Thumbs up An advocacy campaign to raise awareness on down syndrome in the Philippines - Pecho, Raymund Sigfreid G. (2013)
Opportunities for Filipinos with Down syndrome is much lesser compared to those people with Down syndrome in other countries. Aside from the discrimination Filipinos with Down syndrome are getting, awareness on the condition in the country is lesser than in other parts of the world where there are countless efforts on telling what people with Down syndrome are capable of doing and becoming. With proper guidance, encouraging, enabling and empowering, Filipinos with Down syndrome would be able to discover their interests and potentials ad would be able to live normal and productive lives like those people with Down syndrome in other countries. Through photographs, the campaign posters, billboards and videos will acts as testimonials that tell of what people with Down syndrome can do and become. The campaign aims to encourage families of Filipinos with Down syndrome to Encourage, Enable and Empower their children through love, support, proper guidance and early intervention.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Down syndrome